A Quick Diagnosis to Determine the Potential of Payment for Ecosystem Services in Hydrographic Micro-basins - Huertas, German (2010)
The guide is based on four components of analysis: supply and demand conditions of water ecosystem services, governance and institutional framework; criteria and indicators are established and evaluated for each component. The fast diagnose defines the immediate actions needed to overcome the weaknesses of the components and to strengthen the conditions for the design and implementation of a scheme of payment for water ecosystem services. We present the results of the implementation and validation of the guide on the microwatershed of the Reventado River in Cartago, Costa Rica, according to which, in general, this microwatershed has favorable conditions for the design and implementation of a PWES schema. There were identified and prioritized, through a participatory procedure, some immediate actions, that should be implemented to perform a payment for water ecosystem services in this microwatershed.